1999
DOI: 10.1136/bmj.319.7222.1408
|View full text |Cite
|
Sign up to set email alerts
|

Overnight calls in primary care: randomised controlled trial of management using nurse telephone consultation

Abstract: We recently published the results of a randomised controlled trial of a nurse telephone consultation service in primary care out of hours. 1 The new service, operating at evenings and weekends, significantly reduced general practitioners' workload and was at least as safe as the existing out of hours service. Contacts diminish sharply after about 10 pm, 2 and, anecdotally, a higher proportion of night calls necessitate consultation with a general practitioner. We report here a parallel trial aimed at establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 3 publications
0
41
0
1
Order By: Relevance
“…70 Two RCTs comparing triage by GPs and nurses in out-of-hours primary care settings found no difference in hospital admissions. 5,15 Richards et al, 3 however, found an increase in A&E admissions following nurse telephone triage in general practice. 3 McKinstry et al 72 suggested that telephone consultations may be less likely to include sufficient information to exclude important serious illnesses and therefore were potentially more likely to compromise patient safety.…”
Section: Safetymentioning
confidence: 99%
“…70 Two RCTs comparing triage by GPs and nurses in out-of-hours primary care settings found no difference in hospital admissions. 5,15 Richards et al, 3 however, found an increase in A&E admissions following nurse telephone triage in general practice. 3 McKinstry et al 72 suggested that telephone consultations may be less likely to include sufficient information to exclude important serious illnesses and therefore were potentially more likely to compromise patient safety.…”
Section: Safetymentioning
confidence: 99%
“…Studies of the effect of triage on workload have been small and had a restricted focus (for example, calls in the morning only,3 out of hours,24 and home visit requests received before 10 30 am4). Triage has been reported to reduce general practitioners' same day activity by between 25% and 49%, 3 4 24 but only one small study examined use of services after triage.…”
Section: Introductionmentioning
confidence: 99%
“…Seventeen studies reported impacts on their own service or other services, either from increased or reduced service use and or increased or reduced staff workload [68][69][70]86,95,98,99,[101][102][103]105,109,112,114,122,126,134 One study found that NHS Direct referred a higher proportion of patients to other services when compared with general practice. 134 A RCT by Lattimer et al 68 reported a 38% reduction in primary care appointments and a 23% reduction in home visits, whereas another study reported no change in primary care appointments but home visits reduced by 18%.…”
Section: Service Impactsmentioning
confidence: 99%